CAN A 3-MONTH HANDBALL TRAINING CHANGE ANTHROPOMETRIC PARAMETERS AND CARDIOVASCULAR RESPONSES IN ADOLESCENTS AGED 14 TO 18 YEARS? (Fiep Bulletin - online, 2012)
Introduction: The practice of regular physical activity promotes important changes in cardiovascular performance,and produce changes in anthropometric parameters and body composition. Objective: To evaluate changes in anthropometricand cardiovascular adjustments adolescents aged 14 to 18 years, of both sexes, submitted to the handball training of 12 weeks.Methods: The study included 24 adolescents, 11 boys and 13 girls. We evaluated height, weight, body mass index (BMI), bodycomposition and cardiovascular parameters (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterialpressure (MAP) and double product (DP) before and after the period of 12 weeks of training handball. Results: There was asignificant increase (p
Keywords: anthropometry; cardiovascular parameters; handball; physical training